2017
DOI: 10.1080/16000889.2017.1353388
|View full text |Cite
|
Sign up to set email alerts
|

A CO-based method to determine the regional biospheric signal in atmospheric CO<sub>2</sub>

Abstract: Regional-scale inverse modeling of atmospheric carbon dioxide (CO 2 ) holds promise to determine the net CO 2 fluxes between the land biosphere and the atmosphere. This approach requires not only high fidelity of atmospheric transport and mixing, but also an accurate estimation of the contribution of the anthropogenic and background CO 2 signals to isolate the biospheric CO 2 signal from the atmospheric CO 2 variations. Thus, uncertainties in any of these three components directly impact the quality of the bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 87 publications
(106 reference statements)
1
32
1
Order By: Relevance
“…However, this can be due to enhanced CO emissions transported from other European cities towards Beromünster. Oney et al (2017) observed particularly large CO / CO 2 ratios at Beromünster during several pollution events in late winter and early spring 2013 which were associated with air mass transport from eastern Europe, where poorly controlled combustion of biofuels and coal likely results in high ratios.…”
Section: R Co Values From Radiocarbon Measurementsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, this can be due to enhanced CO emissions transported from other European cities towards Beromünster. Oney et al (2017) observed particularly large CO / CO 2 ratios at Beromünster during several pollution events in late winter and early spring 2013 which were associated with air mass transport from eastern Europe, where poorly controlled combustion of biofuels and coal likely results in high ratios.…”
Section: R Co Values From Radiocarbon Measurementsmentioning
confidence: 99%
“…Periods with winds from the east, colloquially known as Bise, are well known to be associated with very stable boundary layers and correspondingly strong accumulation of air pollutants during the cold months of the year between autumn and spring. Air masses reaching Beromünster from eastern Europe have recently been reported to contain unusually high levels of CO during late winter and early spring periods, coinciding with this sampling period (Oney et al, 2017).…”
Section: Calculation Of R Co Co / Co 2 and High-resolution Co 2ffmentioning
confidence: 99%
See 3 more Smart Citations